2021
DOI: 10.7150/ijbs.60866
|View full text |Cite
|
Sign up to set email alerts
|

SEC23A Inhibit Melanoma Metastatic through Secretory PF4 Cooperation with SPARC to Inhibit MAPK Signaling Pathway

Abstract: Metastasis of melanoma to the distant organs is a multistep process in which the tumor microenvironment (TME) may play an important role. However, the relationship between metastatic progression and TME is intricate. In the present study, using melanoma derivative cell lines OL (oligometastatic) and POL (polymetastatic) that differ in their metastatic colonization capability, we have elucidated a new mechanism involving "SEC23A-PF4-MAPK/ERK axis" in which PF4 transported by COPII hinders metastasis through inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Next, we examined whether POL cells can augment the metastatic competency of OL cells via the secretory protein pathway. We have shown previously that Sec23a inhibits metastatic colonization efficiency of melanoma by regulating the transportation of secretory proteins [14,24]. In this study, we first measured whether Sec23a mRNA and protein expression in OL cells were altered upon co‐culture with POL cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we examined whether POL cells can augment the metastatic competency of OL cells via the secretory protein pathway. We have shown previously that Sec23a inhibits metastatic colonization efficiency of melanoma by regulating the transportation of secretory proteins [14,24]. In this study, we first measured whether Sec23a mRNA and protein expression in OL cells were altered upon co‐culture with POL cells.…”
Section: Resultsmentioning
confidence: 99%
“…Fourthly, we prioritized S100A11 from 198 secretory proteins of POL and made the prediction that POL‐secreted S100A11 inhibits Sec23a in OL cells. Our previous studies have shown that Sec23a inhibits metastatic colonization by regulation of the secretome [14,24]. Thus, Sec23a is the initiator of the tumor‐suppressive activity of the Sec23a‐dependent secretome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we discovered that secretory proteins in the paracrine pathway can mediate the communications between tumor cells with different metastatic ability [ 36 ]. Exosomes, a new category of paracrine substances, have more complex contents and higher delivery efficiency [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the available information on PF4 expression in tumor cells is still limited and may vary depending on the specific type of cancer. For example, in oligometastatic melanoma cells, Pf4 knockout increases cell migration in vitro and lung metastasis formation in vivo 64 . Similarly, in human head and neck cancer tumor cells, Pf4 overexpression reduces tumor growth and increases survival 65 .…”
Section: Discussionmentioning
confidence: 99%